1995
DOI: 10.1210/mend.9.8.7476994
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional differences in the dio1 gene in mice with inherited type 1 deiodinase deficiency.

Abstract: The type 1 deiodinase (D1) provides the major portion of the circulating T3 in vertebrates. In C3H and certain other inbred mice, liver and kidney D1 activity is 5- to 10-fold lower than in the common phenotype, C57. The lower D1 levels are paralleled by a decreased normal-sized dio1 mRNA and hyperthyroxinemia. Low activity cosegregates with a restriction fragment length variant (RFLV) in both inbred and recombinant strains, indicating it is due to differences in the dio1 gene. The exonic structure and the ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…The INR sequences of the mouse and human genes are identical, and mdio1 also has the SP1-binding site. The human and mouse promoters have 72% identity over the 260 bp 5Ј to the TSS (41). The hdio1 mRNA is T3 responsive in HepG2 cells and the increase of both rat dio1 and hdio1 mRNAs is not blocked by 30 min of preincubation with cycloheximide, indicating that this response does not require protein synthesis or the presence of short-lived proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The INR sequences of the mouse and human genes are identical, and mdio1 also has the SP1-binding site. The human and mouse promoters have 72% identity over the 260 bp 5Ј to the TSS (41). The hdio1 mRNA is T3 responsive in HepG2 cells and the increase of both rat dio1 and hdio1 mRNAs is not blocked by 30 min of preincubation with cycloheximide, indicating that this response does not require protein synthesis or the presence of short-lived proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse dio1 gene (mdio1) consists of four exons and a TATA-less promoter which is GC rich and contains an SP1-binding site (41). No TREs in the 5Ј-flanking region of that gene have yet been identified despite the fact that mdio1 mRNA increases rapidly after T3 administration in vivo (41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main thyroid gland hormonal secretion is thyroxine (T 4 ), which is then deiodinated to generate tri-iodothyronine (T 3 ), the most active thyroid hormone (Maia et al 1995, Yen 2001. Types I, II, and III iodothyronine deiodinases (D1, D2, and D3 respectively) regulate T 3 production and clearance via removal of specific iodine atoms from the precursor molecule T 4 or T 3 itself.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that T 3 and retinoids induce the expression of the Dio1 gene via two complex thyroid hormone response-retinoic acid response elements located in the promoter region of the human Dio1 gene (66). Although both the rat and mouse liver Dio1 mRNAs are markedly increased by T 3 , canonical thyroid hormone response elements (TREs) have not yet been identified in the available 5Ј-flanking regions (5Ј-FR) of these genes (9,35,36).…”
mentioning
confidence: 99%